Design of Special Mechanism of Slaughterhouse Retribution at Traditional Events in North Toraja - Ade Lisa Matasik; Stefani Marina Palimbong; Iindarda Sakung Panggalo (GoAcademica Research & Publishing, 2022)
The traditional rambu tuka’ and rambu solo’ events are inseparable from the life of the Toraja people. In this traditional event, livestock such as pigs and buffalo are usually slaughtered. Due to the slaughter of animals in traditional events, a slaughterhouse levy is imposed following Regional Regulation No. 15 of 2011. This study aims to evaluate the implementation of the existing RPH levy collection and to design a unique mechanism for traditional events based on applying basic principles in taxation and the internal control system (SPI) in the revenue accounting field system. This study uses descriptive qualitative research by conducting direct observations and interviews. The location of the research will be at the Regional Revenue, Financial, and Asset Management Office (DPPKAD) and the location of traditional events in North Toraja Regency. The primary data are the observations and interview results, secondary data, related rules, and other supporting documents. The results of this study indicate that the mechanism for collecting Slaughterhouse levies is quite good, but there are still some things that still need attention, especially those related to the levy principle and the internal control system in the revenue accounting system.